Visto, si stupri. Sesso e terrore nelle immagini di violenza sulle donne nel cinema italiano degli anni Settanta, tra finzione e realtà (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
In the 1970s, Italian cinema experienced a boom of images and narrative elements associated with acts of violence against women, which were often further combined with sex. Such a phenomenon characterized domestic film production to a very large extent, therefore beyond budget and marketing implications, as well as auteur ambitions. In this context, the mystery-thriller films of the so-called “giallo” established a peculiar relation with violence against women at large, as they encoded it in the narrative mechanisms and in the development of the genre itself by means of subject-related marketing strategies and audience expectations. Quickly brought to popularity in the wake of Dario Argento’s works, over the years the “giallo” has been widely investigated precisely on the grounds of its defining featuring of violence against women, with most outcomes interpreting its psychological and allegorical aspects against the background of Italy’s contemporaneous social history. The aim of this essay is to enrich the interpretation field on this subject, prompting a reflection on such images and imagery of violence in the light of what were the practices, beliefs and expectations about violence against women beyond fiction, in the everyday life of 1970s Italy.